Loss and Gain in Translation of Culture-Specific Items in Ahmad Tohari’s Lintang Kemukus: A Semantic Study - Leni Tiwiyanti; Ayu Bandu Retnomurti (Lingua Cultura, 2017)
Culture-specific items (CSIs) are difficult to translate since they are related to cultural knowledge and cultural background of the given culture. The distance and differences between two different cultures determine the extent of the gain or loss that will be exprienced by the CSIs as they are translated. From Indonesian into English The purposes of this research were to identify the translation procedures applied in translating CSIs which caused loss and gained in the translation process and to identify how the translator compensated the loss in translating CSIs. The method used was qualitative descriptive method. The result shows that loss is more prevalent than gain although the translator has enough knowledge on the source text culture as he has spent some years doing some researches in Banyumas society. There are two kinds of losses found in this research; inevitable and avertable losses. Translation procedures used which result in loss in translation are translation by a more general word (subordinate), translation by a more neutral/less expressive word and translation by cultural substitution. Gain is realized mostly through the creativity of the translator when they are able to explain the culture-specific items for effectivecommunication. In order to compensate the loss that might have occurred, translator uses some translation procedures. They are translation by loan word with explanation, translation by paraphrase using related word, and translation by paraphrase using unrelated word. In short, gain in translation for better communication is not easy to achieve especially in the case oftranslating CSIs.